2015
DOI: 10.7567/jjap.55.01aa15
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature synthesis of carbon nitride by microwave plasma CVD

Abstract: Investigation of the low temperature synthesis of carbon nitride was carried out by microwave plasma CVD. Carbon nitride was synthesized using an improved microwave plasma CVD apparatus. Si was used as the substrate. A mixture of CH4 and N2 gas was used as a reaction gas. Synthesis pressure was varied from 1.1 to 4.0 kPa, microwave power was varied from 400 to 800 W. Faceted particles were obtained at a microwave power of 800 W and a substrate temperature of 880 K. Faceted particles were obtained at various sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Nitrides Nitrides are another class of nitrogen-containing compounds based on metal-nitrogen bonds. Examples include boron nitride, [37][38][39][40] carbon nitride, [41][42][43][44][45] silicon nitride, 46) gallium nitride, [47][48][49][50][51][52][53] indium nitride, 54) aluminum nitride, iron nitride, titanium nitride, tantalum nitride, tungsten nitride and hafnium nitride. Methods for the deposition of atomic layers of these compounds are listed in Ref.…”
Section: Nitrogen Derivativesmentioning
confidence: 99%
“…Nitrides Nitrides are another class of nitrogen-containing compounds based on metal-nitrogen bonds. Examples include boron nitride, [37][38][39][40] carbon nitride, [41][42][43][44][45] silicon nitride, 46) gallium nitride, [47][48][49][50][51][52][53] indium nitride, 54) aluminum nitride, iron nitride, titanium nitride, tantalum nitride, tungsten nitride and hafnium nitride. Methods for the deposition of atomic layers of these compounds are listed in Ref.…”
Section: Nitrogen Derivativesmentioning
confidence: 99%
“…Some reports showed that crystalline deposits are obtained when using CVD. α-C3N4 was obtained from a mixture of CH4-N2 reaction gas systems using microwave plasma CVD (Tanaka and Sakamoto, 2016), and graphitic C3N4 (g-C3N4) was obtained by thermal CVD (Tanaka and Sakamoto, 2017). Nevertheless, a super-hard carbon nitride film has not been realized.…”
Section: Introductionmentioning
confidence: 99%